2016
DOI: 10.1016/j.gene.2015.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heparin on the biological properties and molecular signature of human mesenchymal stem cells

Abstract: Chronic use of heparin as an anti-coagulant for the treatment of thrombosis or embolism invokes many adverse systemic events including thrombocytopenia, vascular reactions and osteoporosis. Here, we addressed whether adverse effects might also be directed to mesenchymal stem cells that reside in the bone marrow compartment. Harvested human bone marrow-derived mesenchymal stem cells (hMSCs) were exposed to varying doses of heparin and their responses profiled. At low doses (<200 ng/ml), serial passaging with he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 70 publications
3
67
0
2
Order By: Relevance
“…Heparin has been previously shown to influence the MSC proliferation, phenotype, and biological properties (33). Modification in biological properties may affect the differentiation capability of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin has been previously shown to influence the MSC proliferation, phenotype, and biological properties (33). Modification in biological properties may affect the differentiation capability of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…5C). sGAG, in particular Hep and heparan sulfate, have been reported to promote osteogenesis of BMSC63553. Effects have been strongly dependent on cellular systems, detailed sGAG properties (doses, molecular weight, number of sulfate residues per disaccharide unit (degree of sulfation D.S.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that supplementation of hMSC cultures with the generic hyper‐sulfated glycosaminoglycan (GAG) heparin, results in adverse changes in the biological properties of the cells . However, HS preparations can selectively bind FGF‐2 and potentiate its signaling , improving growth and potency of hMSCs .…”
Section: Introductionmentioning
confidence: 99%